AGILE FROM FIRST PRINCIPLES - GIRVAN, LYNDA. GIRVAN, SIMON (BCS, THE CHARTERED INSTIT, 2022)
Agile principles and values transform the way organisations carry out business and respond to change. To realise success, an agile mindset needs to be adopted throughout an organisation, not just within the IT team.This book is an introductory guide to agile principles, values and mindset that will equip individuals and teams, regardless of role, to apply Agile from first principles. Practical examples are used throughout to illustrate agile theory with real-world context. This book is ideal for those wanting to achieve the BCS Foundation Certificate in Agile.
Keywords: Management information systems.; Organizational effectiveness.; Business planning.; Information technology.; Agile software development.; Continuous improvement process.; elektronické knihy; electronic books